Looking through the Ethnolinguistic Perspective to Unveil the Social Facts Phenomenon of Piil Pesenggiri - Ninsiana, Widhya (Universitas Negeri Semarang, 2018)
This article discusses the issues around the socio-cultural phenomenon that employ interdisciplinary studies between linguistics, anthropology and sociology to study the linguistic behaviors of the Lampungese society in a way to grasp their worldview. The data were technically collected through observation and literature reviews to bring out the voices and experiences of the people who mostly affected by the concept of Piil Pesenggiri, of people whose voices have been missing in literature and debate. The production and reproduction of identity through Piil Pesenggiri seems to remain a finding tradition exist among the Lampungese which primarily resulted both demographic and the local political change allowing emergence of a capitalist strategy